Trematode diversity in freshwater fishes of the Globe I: 'Old World' - Scholz, Tomáš; Besprozvannykh, Vladimir V; Boutorina, Tamara E; Choudhury, Anindo; Cribb, Thomas H; Ermolenko, Alexey V; Faltýnková, Anna; Shedko, Marina B; Shimazu, Takeshi; Smit, Nico J (Systematic parasitology, 2016)
In this paper, we review, continent by continent, the trematode fauna of freshwater fishes of the 'Old World', a vast area consisting of the Palaearctic, Ethiopian, Oriental and Australasian zoogeographical regions. Knowledge of this fauna is highly uneven and clearly incomplete for almost all regions, sometimes dramatically so. Although the biggest problem remains the completion of the 'first pass' of alpha taxonomy, there are in addition great problems relating to biogeography and elucidation of life-cycles. For the latter, molecular data, i.e. matching DNA sequences of larval stages and corresponding adults, may represent a powerful tool that should be used in future studies. Another challenging problem represents the existence of cryptic species and, in particular, considerable decrease of experts in taxonomy and life-cycles of trematodes.
Keywords: Australasia; Evropa; Europe; genetické techniky; Animals; Fresh Water; Afrika; Asia; Asie; Larva; Genetic Techniques; Australasie; sladká voda; Classification; klasifikace; Africa; Fishes; zvířata; Biodiversity; larva; ryby; Trematoda; biodiverzita